Model-Model Standarisasi Manajemen Mutu (SMM) ISO-IWA dalam Pendidikan - Nurul Fauziah; Sitti Fatimah Azzahra; Fahmi Parmansyah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This article is intended to express the standard of quality management ISO-IWA in education. Elements of change and implication in the field of education. The result shows that the field of education to implement SMM ISO9001:2008 focus on school satisfaction towards quality standards of education. The are many profits to be gained from the education institute status standard of quality management ISO-IWA, principle the standard of quality management ISO with judgment various to enhancement and development standard international. A guide in implementation ISO (International Organization for Standardization) compiled the mechanism workshop, and not through the committee process, International Workshop Agreement approved by consensus among the participants.